PRE SERVICE BIOLOGY TEACHERS’ ARGUMENTATION SKILLS IN ANIMAL PHYSIOLOGY LABORATORY - Amin, Astuti Muh. (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
Empowering argumentation skills is very important to improve the quality and complexity of students’ knowledge. An individual’s conceptual understanding and reasoning can be evaluated from his/her ability to provide either written or spoken arguments. This study was conducted to examine the pre-service biology teachers’ argumentation skills with 142 pre-service biology teachers from South Sulawesi as research subjects. Based on Toulmin Argumentation Pattern rubric, pre-service biology teachers’ argumentation skills were categorized as low. It is necessary to improve the quality of the pre-service biology teachers’ argumentation skills such as by implementing a particular learning model or strategy.